Influence of probiotic bacterium Lactobacillus acidophilus on the survival and growth of pearl oyster Pinctada fucata spat - Subhash, S K; Lipton, A P; Paulraj, R (Indian Journal of Fisheries, 2011)
Combination of micro-alga Chaetoceros calcitrans and the probiotic bacterium Lactobacillus acidophilus evaluated at 1:1 and 1:2 levels revealed that in the probiotic treated group, Pinctada fucata spat registered significantly high survival of 79.7 and 89.0 % (P<0.05) respectively compared to that of 65.0 % survival in control. The probiotic treated groups also showed significant improvement in growth in terms of length and weight as compared to the control group. The probiotic treated spat attained a weight gain of 346.0 ± 1.57 mg (1:1 level) and 382.0 ± 11.76 mg (1:2 level) compared to 296.4 ± 9.04 mg in control group. The length in terms of dorso-ventral measurement (DVM) increased to 18.68 mm (1:1 level) and 19.6 (1:2 level) mm compared to 13.56 mm in control group